Unpacking multidimensional effects of economic restructuring and technological progress on carbon emission performance: the moderating role of environmental regulation - Yin, Jin; Ibrahim, Saifuzzaman; Mohd, Naseem Niaz Ahmad; Zhong, Cheng; Mao, Xiaoming (Nature Research, 2025)
The growth in carbon emissions poses a severe challenge to global sustainable development, making it imperative to explore the impacts of economic restructuring and technological progress on Carbon Emission Performance (CEP). However, existing studies often lack an integrated analysis of economic restructuring and technological progress, while giving limited attention to the indirect role of Environmental Regulation (ER). This study constructs a multidimensional theoretical framework, breaking down economic restructuring into four dimensions—industrial structure, factor input, ownership, and new-type urbanization (NTU), and refining technological progress into technological innovation and energy efficiency. It uncovers the complex interplay among CEP, economic restructuring, technological progress, and ER. The findings reveal critical insights: (1) industrial structure suppresses CEP, whereas adjustments in factor input and ownership structure significantly enhance it; (2) the relationship between NTU and CEP exhibits a non-linear pattern; (3) compared to the technological innovation, energy efficiency provide a more substantial boost to CEP; and (4) ER positively moderates the impacts of factor input, ownership structure, and NTU. Finally, the study proposes recommendations for holistic economic restructuring and diversified ERs.